Dental Health Educational: Media Videos and Animated Videos on Increasing Dental and Oral Health Maintenance Behavior - Suwarsono Suwarsono; Lilis Ayu Safitri; Lanny Sunarjo (Journal Center of Excellent : Health Assistive Technology, 2023)
Dental health education in children is an effort that can emotionally eliminate fear, want to observe, and foster curiosity so that children physically perform activities that are demonstrated for their health. The selection of dental health education media must be considered in detail and carefully so that the media displayed can have an effect on increasing children's behavior in maintaining oral health. The purpose of this study was to determine the difference in the effectiveness of dental health education with dental health education video media and animated videos on improving the oral health maintenance behavior of 4-5 grade students of Brebes 14 State Elementary School. Research Methods Quasi experimental with pre and post-test design with Two Group Design. The sample used in this study was 60 students of Brebes 14 State Elementary School with purposive sampling technique. Data analysis using univariate and bivariate analysis, namely the Wilcoxon test to prove whether there is a change in oral health maintenance behavior before and after being given dental health education and the Mann-Whitney test to determine the effectiveness of the two dental health education media. The results of the Wilcoxon test showed that the average value of dental health maintenance behavior with dental health education video media was 47.3. Dental health maintenance behavior with animated video media is 43.9. And the Mann-Whitney test results show significant results p-value = 0.000 <0.05. It can be concluded that dental health education with dental health education video media is more effective in improving oral health maintenance behavior compared to using animated video media with a p-value <0.05.